The management of programs mais educação e escola a tempo inteiro: an analysis of policies for full-time education - Schimonek, Elisangela Maria Pereira; Adrião, Theresa (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
The present study aims to promote an analysis of two government programs for full-time education in Brazil (Programa Mais Educação) and Portugal (Programa Escola a Tempo Inteiro), focusing on their management, both in the system and in the school setting, observing their scope and organization, stated objectives, actors mobilized and sources of resources. The Programa Mais Educação (PME) was aimed at low Ideb schools and / or located in regions of social vulnerability and promoted the selection of the learners according to criteria defined in their official documents. The Programa Escola a Tempo Inteiro (PETI) included all primary schools and students from Continental Portugal in the 1st cycle (1st to 4th grade) of elementary education. This is a qualitative study, supported by bibliographic review and documentary analysis of primary (legislations, documents and official publications) and secondary sources, which demonstrated the existence of two Programs with differentiated organizations, but with the same purpose: to act on educational inequalities, as a means of guaranteeing the improvement of the educational results obtained in external evaluations, admitting, to this end, the presence of the private sector to share actions of full-time education. The time cut used for the analysis of PME and PETI was 2008-2013.